Improving the competence and confidence of pulmonary and critical care medicine fellows in performing a cricothyrotomy - Rajwani, Kapil; Mauer, Elizabeth; Clapper, Timothy C. (Revue canadienne de l'éducation médicale, 2019)
Clinical opportunities to practice or perform a cricothyrotomy are limited. We developed an evidence-based cricothyrotomy course following the 4-phase lesson plan for simulation that provides pulmonary and critical care medicine fellows with demonstrations, practice, and feedback to increase their confidence and competence.Survey results demonstrated an improvement in perceived confidence (p<0.005) and competence (p<0.002) following this educational intervention. Fellows also achieved significant improvement in knowledge (p<0.003) and performance in two cricothyrotomy techniques (Seldinger and MacIntyre) (p<0.004).It is important that we provide fellows with practice opportunities that can be used to develop and maintain proficiency, particularly in low frequency events.